2013
DOI: 10.1038/srep01668
|View full text |Cite
|
Sign up to set email alerts
|

Turning Oscillations Into Opportunities: Lessons from a Bacterial Decision Gate

Abstract: Sporulation vs. competence provides a prototypic example of collective cell fate determination. The decision is performed by the action of three modules: 1) A stochastic competence switch whose transition probability is regulated by population density, population stress and cell stress. 2) A sporulation timer whose clock rate is regulated by cell stress and population stress. 3) A decision gate that is coupled to the timer via a special repressilator-like loop. We show that the distinct circuit architecture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…This approach enables us to investigate the effect of the number of the microRNA binding sites on the mRNA. We found that the [miR-34/SNAIL] module is a monostable circuit that acts as a noise-buffering integrator, reminiscent of the bacterial sporulation sensing system (25)(26)(27). The [miR-200/ZEB] module was found to be a tristable circuit that acts as a ternary switch.…”
Section: Significancementioning
confidence: 99%
“…This approach enables us to investigate the effect of the number of the microRNA binding sites on the mRNA. We found that the [miR-34/SNAIL] module is a monostable circuit that acts as a noise-buffering integrator, reminiscent of the bacterial sporulation sensing system (25)(26)(27). The [miR-200/ZEB] module was found to be a tristable circuit that acts as a ternary switch.…”
Section: Significancementioning
confidence: 99%
“…However, recent work Kuchina et al (2011) showed that slow progression to sporulation and excursions to competence occurs independently and concurrently up to a certain irreversible decision point, and the choice of the phenotype depends on the outcome of a “molecular race” between the two independently progressing differentiation programs: whichever program reaches the decision point first, wins. On the other hand, the decision circuit itself appears to have non-trivial oscillatory that transiently open so-called “windows of opportunity” for competence Schultz et al (2013).…”
Section: Stochasticity In Cell Biologymentioning
confidence: 99%
“…The present theoretical approach brings to light that Hes1 oscillation actually keeps in balance a labile proliferation state and two competing cell fate outputs associated with distinct Hes1-high and Hes1-low cell cycle arrest states, the outcome of which depends on the relative sensitivity of neighboring cells to extracellular signaling cues stabilizing Hes1 expression at either high or low levels. Hes1 oscillation thus maintains a highly dynamic precommitment state that is well-equipped with a wealth of decision-making properties, such as decision gates through signal timing sensitivity (Schultz et al, 2013;Pfeuty and Kaneko, 2014) or population-level decisions finely tuned by synchronization/ desynchronization mechanisms (Lewis, 2003;Suzuki et al, 2011;Wang et al, 2011). For the latter, lateral inhibition constitutes a powerful intercellular coupling mechanism for promoting reliable cell fate decisions while maintaining cell type diversity .…”
Section: Developmental Cell Fate Decisions Through Oscillatory Dynamimentioning
confidence: 99%